1984
DOI: 10.3109/00365598409180207
|View full text |Cite
|
Sign up to set email alerts
|

Cystadenoma of the Seminal Vesicle

Abstract: Cystadenomas of the seminal vesicle are extremely rare benign tumours, which only have been reported seven times earlier in the literature. The first Danish case is reported with discussion of symptomatology, pathology and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Mixed epithelial‐stromal tumors of seminal vesicle are extremely rare, and a review of the literature has revealed only 14 previous cases 1–13 . These cases were reported using various terminology, including cystomyoma, cystadenoma, mesonephric hamartoma, papillary cystadenoma, cystic epithelial‐stromal tumor, müllerian adenosarcoma‐like tumor and cystosarcoma phyllodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixed epithelial‐stromal tumors of seminal vesicle are extremely rare, and a review of the literature has revealed only 14 previous cases 1–13 . These cases were reported using various terminology, including cystomyoma, cystadenoma, mesonephric hamartoma, papillary cystadenoma, cystic epithelial‐stromal tumor, müllerian adenosarcoma‐like tumor and cystosarcoma phyllodes.…”
Section: Discussionmentioning
confidence: 99%
“…Cystadenoma was characterized by variable‐sized cysts lined by cuboidal to columnar cells and a low cellularity of the stroma. Mitotic figures were absent in both tumor components 3–6 , 8–10,12 , 13 . Mesonephric hamartoma was characterized by hamartomatous growth of glandular, smooth muscle and vascular tissues with distortion of the normal tissue architecture 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been scattered reports of seminal vesicle cystadenomas, since Soule and Dockerty 3 reported ‘cystadenoma of the seminal vesicle’. Overall, previous reports 4–6 reveal that the gross pathology of a neoplasm typically shows a multilobulated, cystic tumor containing cleft‐like spaces filled with a brownish to yellow, viscous or soft gelatinous fluid. Microscopic examination has shown the cystic area to be lined with a single layer of columnar or cuboidal epithelium surrounded by a fibrous stroma, which is a leading feature 4,5 .…”
Section: Discussionmentioning
confidence: 88%
“…There are no definite recommendations for a clinical evaluation and management, because so few cases of cystadenoma have been reported. Three cases underwent a fine needle biopsy; one of which showed only benign epithelial cells, 6 another case was inconclusive despite the repeated aspiration biopsy, 4 and the other case showed focal atrophied and inflammatory change in gland and edematous expansion in stroma 5 . It might seem that diagnosis based on needle aspiration biopsy was not appropriate because of multilocular organization.…”
Section: Discussionmentioning
confidence: 98%